Pengaruh Keputusan Investasi, Kebijakan Hutang Dan Kebijakan Dividen Terhadap Nilai Perusahaan - Ivan Somantri; Hadi Ahmad Sukardi (Jurnal Ekonomi Manajemen Perbankan, 2019)
This study aims to determine how to influence simultaneously and partially investment decisions, debt policy and dividend policy on firm value in mining sector companies listed on the Indonesia Stock Exchange for the period 2013-2017. The research method used in this study is descriptive and associative methods. The population in this study were mining sector companies listed on the Indonesia Stock Exchange in the period 2013-2017, which amounted to 43 companies. The sampling technique used in this study is non probability sampling with purposive sampling method, so that the number of samples obtained is 8 companies. While the data analysis used in this study is panel data regression analysis with the fixed effect method. The results of the study show that partially investment decisions and debt policies have a positive effect on firm value. While dividend policy has a negative effect on firm value. In addition, the results of the study simultaneously show that investment decisions, debt policies and dividend policies affect the value of the company. The amount of investment decisions, debt policy and dividend policy in contributing influence to earnings management is 34.14%.